Influence of Dutch Disease to International Trade of Venezuela - Karimov, Hamid; Stroukal, Dominik, 1987-; Nikolovová, Pavla, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
This thesis proves that Venezuela is going through the so called <Dutch disease> and shows all the effects of this disease to international trade indicators and finally evaluates which proposal how to help Venezuela to deal with it is most in line with the empirical data from World Bank and FRED. All the empirical evidences for Dutch disease worldwide effects are demonstrated on Oman, Kazakhstan, Azerbaijan, Ghana and Norway. The hypothesis about influences of Dutch disease on international trade of Venezuela was proved and discussed by correlation analysis. Among key focused metrics are included GDP growth, Exports and Imports of goods and services, Unemployment, General government final consumption expenditure and Real effective exchange rate.
Vedoucí práce: Dominik Stroukal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses